Copper‐Functionalized Silica‐Coated Magnetic Nanoparticles for an Efficient Suzuki Cross‐Coupling Reaction. Issue 3 (19th January 2021) - Sonei, Samin; Taghavi, Faezeh; Khojastehnezhad, Amir; Gholizadeh, Mostafa
Abstract: In this study, a new, efficient and inexpensive strategy has been developed based on the heterogeneous copper catalyst for the synthesis of different biaryl compounds via the Suzuki–Miyaura cross‐coupling reaction. In this respect, the core@shell modified Fe3 O4 @SiO2 magnetic nanoparticles (MNPs) has been prepared by immobilization of aminoguanidine and then the copper (II) ion into the surface of magnetic nanoparticles. After full characterization of the prepared catalyst by various technique such as TEM, SEM, EDX, TGA, XRD, VSM, ICP and FT‐IR, its catalytic activity has been investigated in the synthesis of different biarly compounds through the Suzuki‐Miyaura cross‐coupling reaction. Interestingly, similar to Pd‐based catalysts, this new heterogeneous Cu‐based catalyst can catalyze the Suzuki–Miyaura reaction in solvent free condition with good to excellent yields. Besides, this heterogeneous nano copper catalyst was able to separate from the reaction mixture by easy separation procedures and can reuse more than six runs. Abstract : In this study, a new, efficient and inexpensive strategy has been developed based on the heterogeneous copper catalyst for the synthesis of different biaryl compounds via the Suzuki–Miyaura cross‐coupling reaction. Interestingly, similar to Pd‐based catalysts, this new heterogeneous Cu‐based catalyst can catalyze the Suzuki–Miyaura reaction in solvent free condition with good to excellent yields. Besides, this heterogeneous nano copper catalyst was able to separate from the reaction mixture by easy separation procedures and can reuse more than six runs.